Evaluation of IT Resource Management Capability Using COBIT 5 on Subdomain EDM04 and APO07 - Carissa Renatasari; Anita Wulansari; Eristya Maya Safitri (bit-Tech, 2025)
The Population and Civil Registration Office of Sidoarjo Regency is a government agency that implements performance-based management, focusing its activities on service excellence and utilizing information technology in its services such as the Population Administration Information System (SIAK) and "Plavon". However, there are problems that hinder progress include low public awareness in updating population data, insufficient staff based on Permenpan standards, and the focus on technology-based service innovations. To address these, employees are key in community education and supporting priority programs. This research aims to evaluate the level of IT resource management capability at Disdukcapil Sidoarjo using the COBIT 5 framework, focusing on EDM04 (Ensure Resource Optimisation) and APO07 (Manage Human Resources). The methods used based on the COBIT 5 Assessment Process. Both EDM04 and APO07 processes achieved Level 1 Performed Process with "Largely Achieved" status. EDM04 scored 72% overall (69% Base Practices, 75% Work Products), while APO07 scored 64.4% overall (53.7% Base Practices, 75% Work Products). The final results of both scores fall into the "Largely Achieved" category. There is a capability gap between the current condition (as is) and target expectations (to be) of four levels in the EDM04 process and one level in the APO07 process, so improvement recommendations are provided to achieve the expected level. This research provides an overview of current conditions and improvement recommendations to enhance the effectiveness of IT resource management at Disdukcapil Sidoarjo.